Recent Advances in Local Anesthesia Techniques and Agents - Deb, Rahul; Saha, Puja; Debnath, Ashim (Journal of Neonatal Surgery, 2025)
Recent advances in local anesthesia techniques and agents represent significant developments in pain management during dental and surgical procedures. Innovations such as enhanced delivery methods, novel anesthetic agents, and improved pain control strategies have optimized patient comfort and outcomes. This paper explores the latest techniques, including the use of computer-controlled local anesthesia delivery systems, the introduction of new anesthetic agents with fewer side effects, and the application of regional anesthesia techniques that provide longer-lasting effects. Understanding these advancements is essential for practitioners to deliver safe and effective care, ultimately enhancing the patient experience and improving procedural success.